The impact of institutional performance on payment dynamics: evidence from the Italian manufacturing industry - Falavigna, Greta; Ippoliti, Roberto (Journal of Business Economics and Management, 2020)
This work aims to shed new light on the relation between institutional performance and firm dynamics. Considering the Italian manufacturing industry and a panel of 3 years, the authors investigate the relation between the time needed by courts to enforce debtors’ obligations and the time needed by enterprises to repay their debts. In particular, we test the hypothesis that efficiency in settling mortgage foreclosure and bankruptcy cases can affect the creditors’ decision making on judicial disputes. According to our thesis, inordinately long waiting times to enforce credit rights may increase the contractual strength of debtors, further delaying payments. As shown by our results, there is a statistically significant positive relation between the enforcement of debtors’ obligations and the adopted payment index, confirming the key role of the judiciary in the dynamics of firms. Indeed, if the time needed to settle bankruptcy cases decreases by 25%, we can expect the payment index to decrease by 1%; while, focusing on foreclosure cases, we can expect the payment index to decrease by 2%. The policy implications of these results are rather compelling. Policy makers could reform foreclosure and bankruptcy procedures to support national economic growth, without additional burden on the public budget.